Diffusion efficiency of innovation among EU member states: A Data Envelopment Analysis - Henry Anderson; Jan Stejskal (Economies, 2019)
Innovation, in contemporary times, has been established as the lynchpin of growth and national competitive advantage among countries. Supranational and national resources have jointly combined to create sound innovation strategies and diffusion policies for member states in recent times. However, there is the question of whether increased innovation translates to effective diffusion of innovation. With this in mind, the present research aims to comparatively assess and evaluate the efficiency of diffusion of innovation of European Union member states in reference to their European Innovation Scoreboard (EIS) rankings. Using the Charnes, Cooper and Rhodes (CCR) model of Data Envelopment Analysis (DEA), the present research found contrasting diffusion efficiency scores of member states with different innovation performances as most innovative member states had much lower efficiency scores compared to some supposedly weak innovating member states. We also computed the input-redundancy and output-deficiency of member states, provided recommendations for efficient input-output combinations based on findings of respective member states and innovation groups, and finally, outlined directions for future studies.
Keywords: O11; O32; O38; 330; efficiency; diffusion; innovation; European Union; DEA analysis